Grasslands half‐full: investigating drivers of spatial heterogeneity in ungulate occurrence in Indian Terai. (17th November 2021) - Rastogi, S.; Chanchani, P.; Sankaran, M.; Warrier, R.
Abstract: Grassland ecosystems have declined in their extent globally, driving declines in wild ungulate populations. Even within the remnant grasslands, ungulate distribution is highly heterogeneous for reasons that are not well understood. This in turn undermines both local and landscape level conservation efforts for these often‐neglected ecosystems and the herbivores they support. We investigated grassland‐ungulate relationships in the Terai region of North India, where wild ungulates are patchily distributed across alluvial grasslands, a besieged ecosystem. Specifically, we posited that spatial variation in grassland habitat use by swamp deer ( Rucervus duvaucelii duvaucelii ), hog deer ( Axis porcinus ) and spotted deer ( Axis axis ) would be explained by community composition, palatability of key grasses, and fire and flooding regimes in grasslands. Hierarchical clustering and multivariate ordination revealed that three dominant tall‐grass communities and the narrowly distributed and more palatable short grass Cynodon‐Oryza community were only marginally influenced by fire and flood histories. Ungulate habitat use, assessed using occupancy models for spatially correlated data, indicated that hog deer were ubiquitously distributed across the grasslands in the park (habitat use probability, ᴪ = 0.92, se  = 0.05) utilizing a diverse range of grassland types, while spotted deer (ᴪ = 0.80, se  = 0.17) and swamp deer (ᴪ = 0.45, se  = 0.10) occurrence within grasslands was relatively lower. Grass height and grassland extent positively influenced habitat use of swamp deer and spotted deer, respectively. However, grassland community composition, fire history, flood history and palatability were relatively uninformative predictors of fine‐scale habitat use. Our study provides a robust baseline for future monitoring of grasslands and ungulates as well as insights for the design and implementation of grassland management interventions. Abstract : Floodplain grasslands of Himalayan Terai are threatened habitats where herbivore populations in turn have declined dramatically. Even in the remnant grasslands, the distribution patterns of ungulates are heterogeneous, the reasons for which are not well understood. We investigated these grassland‐ungulate relationships in Dudhwa Tiger Reserve, India. Specifically, we explored community composition and palatability of these grasslands and the drivers of grassland use by swamp deer ( Rucervus duvaucelii duvaucelii ), hog deer ( Axis porcinus ) and spotted deer ( Axis axis ). The vegetation analysis revealed three unpalatable dominant grass communities and a palatable spatially restricted Cynodon community. Ungulate grassland use, assessed using an occupancy modelling framework, indicated hog deer to be uniformly distributed across grasslands while swamp deer and spotted deer were restricted to certain grasslands. Grass height and grassland extent positively influenced habitat use of swamp deer and spotted deer, respectively. Our results provide relevant baselines for conservation of these grasslands and associated ungulates.